Vibrio factors cause rapid fluid accumulation in suckling mice. - Nishibuchi, M (1983)
Non-O-1 and O-1 Vibrio cholerae and Vibrio fluvialis isolated from clinical and environmental sources were examined for virulence factor production in 3-day-old suckling mice and in Y-1 tissue culture. The responses of the suckling mice to intragastrically administered bacterial cultures were measured by intestinal fluid accumulation (FA), diarrhea, and mortality. Regardless of the O-serovar, source of isolation, or ability to produce cholera toxin, all strains of V. cholerae stimulated increased FA, which was measurable in the mice at 4 h post-inoculation. The factor(s) causing these symptoms was found to be distinct from cholera toxin by the kinetics of FA and serological difference from cholera toxin based on in vivo neutralization tests. In most instances, FA was followed by high rates of mortality. Y-1 mouse adrenal tumor cell assays also showed that many V. cholerae produced extracellular heat-labile cytotoxic factor(s), and many cholera toxin-negative strains also caused a cytotonic-like morphological response. The majority of V. fluvialis strains produced smaller amounts of cytotoxic factor(s) but no cytotoxic reactions. The factor which stimulates rapid FA in suckling mice could be one of several virulence-associated factors contributing to diarrheal disease by nontoxigenic vibrios, but this is not verified at present.